(untitled) (Research, Society and Development, 2022)
Introduction: easy access to pharmacies and medication purchases makes it a daily practice, this fact has taken on greater proportions in the face of the COVID-19 pandemic and the dissemination of information through digital media. Objective: to verify the prevalence of self-medication in the treatment of COVID-19 among students and teachers. Methods: quantitative, descriptive and cross-sectional study with application of a questionnaire to assess the use of self-medication by students and professors of a higher education institution. Results: 63.6% of the students interviewed had no symptoms for COVID-19, whereas the professors were around 50%, 66.7% of the professors did not take medication to combat the virus, when analyzing the students 36.8% did medication use and the rate of self-medication was around 25% among students and 33% of professors, when asked if the chosen medications were effective even without proof, 34.9% reported that maybe and 18.6% of students informed that yes, 41.7% of the teachers think that such medications can be effective even without scientific evidence. Conclusion: it is noted that even the sample was from a health area environment, it is verified that motivations for beliefs not based on science and evidence-based medicine should be sought.